The appraisal of aspect morphemes in Northern Sotho : a morphological analysis - Matlebjane, Mphurane Josina (My University, 2006)
Refer to the document
Thesis (M. A. (Translation Studies)) -- University of Limpopo, 2006
Keywords: Northern sotho language; Morphemes; Northern Sotho language -- Morphology